hiDoc: Doctor Appointment Booking Web Application - Nur Nadhirah, Yahaya (2023)
Booking a doctor's appointment online is now more convenient and efficient than going to the clinic or making phone calls. There aren't many websites with information on both government and non-government clinics. There are also a few websites that allow patients to book an appointment with the doctor of their choice. For example, there are only a few websites that provide information on clinics in Pekan, Pahang and there is no website that contains information about the clinics in Pekan that allow the Pekan residents to book an appointment with the doctor. Thus, the goal of this project is to allow users to book appointments with government or non-government clinics in district Pekan, Pahang, with the option of selecting the doctor of their choice. There are five modules in this application: manage account, manage appointment booking, manage medical records, manage medicine information, and manage clinic. These modules are implemented following extensive research between existing systems and research papers to create a better doctor appointment booking application that can benefit society.